Escherichia coli O157:H7 risk assessment for blade-tenderized beef steaks - Thippareddi, H.; Sporing, S.; Phebus, Randall K.; Marsden, James L.; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The potential translocation of E. coli O157:H7 from the surface to the interior of whole muscle by blade tenderization was evaluated. Beef top sirloin subprimals were inoculated with 106 or 103 cfu/cm2 and passed once through a Ross blade tenderization unit. Core samples showed a translocation of 3 to 4% of surface inoculum to the geometric center of the subprimal. A second study evaluated thermal destruction of E. coli O157:H7 in blade tenderized (BT) steaks compared to nontenderized (NT) steaks of three thicknesses when ovenbroiled. Subprimal surfaces were inoculated to a level of 107 cfu/cm2 and blade tenderized. Steaks cut from these subprimals were ovenbroiled to internal temperatures from 120 to 170°F, then analyzed for surviving E. coli O157:H7. At internal steak temperatures of 140°F and higher, all E. coli O157:H7 were killed in both BT and NT steaks of all thicknesses. At 130°F, about 5 log reductions were noted for both BT and NT. With oven broiling to even moderate internal temperatures, BT steaks pose no greater risk of E. coli O157:H7 infection than NT steaks.
Keywords: Beef; Blade tenderization; Beef steaks; Risk assessment; E. coli O157:H7